How is “solidarity” understood in discussions about contact tracing apps? An overview - Tretter, Max (Frontiers in Public Health, 2022)
Background: In the context of the SARS-CoV-2 pandemic, there is much discussion about contact tracing apps, their use to contain the spread of the virus as well as the ethical, legal, and social aspects of their development, implementation, acceptance, and use. In these discussions, authors frequently mention ‘solidarity’ when making key points in arguments. At the same time, authors rarely specify how they understand ‘solidarity’. This lack of specification about how they understand ‘solidarity’ can lead to misunderstandings in discussions. Objective: To prevent such misunderstandings, it is important to specify how one understands ‘solidarity’ when mentioning it in the discussions on contact tracing apps. Therefore, the aim of this paper is to elaborate how ‘solidarity’ is understood in the context of contact tracing apps, i.e., how different authors understand ‘solidarity’ when using it in discussions about these apps. Methods: In order to find out how different authors understand ‘solidarity’ when discussing contact tracing apps, I conduct a literature review. I collect papers from several databases, inductively work out central differences and similarities between the different uses of ‘solidarity’, and use them to code and analyze relevant passages. Results: In the final sample, five different understandings of ‘solidarity’ in the context of contact tracing apps can be identified. These understandings differ in how different authors 1. imagine the basic concept of solidarity, i.e., what ‘solidarity’ refers to, 2. how they temporally relate solidarity to contact tracing apps, and 3. how they perceive the causal interactions between solidarity and contact tracing apps, i.e., the different ways in which solidarity and contact tracing apps influence each other. Conclusions: The five understandings of ‘solidarity’ in the context of contact tracing apps presented here can serve as guidance for how ‘solidarity’ can be understood in discussions – thus contributing to a better mutual understanding and preventing communicative misunderstandings.